Las competencias profesionales y su influencia en el diseño del perfil profesional del tecnólogo agropecuario del Instituto Tecnológico Agropecuario Manuel I. Encalada Zúñiga del sitio Pagua cantón el Guabo provincia de El Oro, 2013-2014. - Correa Sosa, Jaime Gonzalo (2015)
The design of methodological strategies to develop competencies in the field of knowledge being, allow the improvement of the professional profile of Agricultural Technologist ITA-MIEZ surpassing the detected external manifestations, insufficient skills development, difficulties in access to employment, limitations teaching in professional and poor manifestation of creative thinking profile.